M. avium binding to HLA-DR expressed alleles in silico: a model of phenotypic susceptibility to sarcoidosis - Saltini, C.; Pallante, M.; Puxeddu, et al., E. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2008)
Sarcoidosis is a systemic granulomatosis disease of unknown origin where a number of microbes, in particular M. tuberculosis and non-tuberculous mycobacteria, have been hypothesized to play a role in disease pathogenesis, possibly through bacterial antigen-driven hypersensitivity. To test this concept, we used bioinformatic tools allowing the identification of antigenic peptides in whole microbial genomes to analyze the interaction between the expressed HLA-DR gene allelic variants and the HLA-DR immunome of all pathogenic bacteria in a population of 149 sarcoidosis affected subjects and 447 controls, all HLA-typed at high resolution. We show here that patients with the Löfgren’s syndrome, express HLA-DR alleles that recognize in silico a significantly higher number of bacterial antigen epitopes compared to the control population (18,496+9,114 vs 17,954+8,742; p